Fostering Mathematical Thinking in Students With Autism Through a Digital Comics - Surianastutiningtyas, Angela Maricilia; Prayitno, Anton (Journal of Education and Learning Mathematics Research (JELMaR), 2023)
This study aims to implement digital comics as a learning medium to enhance mathematical thinking in students with Autism. Students often struggle with understanding abstract concepts and require a visual and structured storytelling approach. Therefore, digital comics offer a combination of narrative, illustrations, and digital interactions that can help them comprehend mathematical concepts more effectively. This study employs an experimental approach with a pretest-posttest design on a group of autistic students at a Special Needs School (SLB) in Malang City. The developed digital comics focus on basic number concepts, including number recognition, simple arithmetic operations, and numerical relationships. Data were collected through mathematical concept comprehension tests, observations of student engagement during learning, and interviews with teachers and parents. The results indicate that the use of digital comics can progressively improve student engagement, mathematical concept comprehension, and mathematical thinking skills. Students demonstrated better recognition of numerical patterns, understanding of number relationships, and the ability to solve simple problems with the aid of engaging visuals. This study provides recommendations for educators to integrate digital comics as an inclusive learning medium that supports students in developing a more meaningful understanding of mathematical concepts.